2020
DOI: 10.3390/en13082088
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Roles of Wastewater Treatment Plants in Sector Coupling

Abstract: The development of a power system based on high shares of renewable energy sources puts high demands on power grids and the remaining controllable power generation plants, load management and the storage of energy. To reach climate protection goals and a significant reduction of CO 2 , surplus energies from fluctuating renewables have to be used to defossilize not only the power production sector but the mobility, heat and industry sectors as well, which is called sector coupling. In this article, the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Recent studies mainly focus on the technical aspects of SC, such as infrastructure optimisation [19], SC facilities [20], or SC solutions like demand and response systems [21]. Other research also tried to include economic considerations of SC [3].…”
Section: Research Demandmentioning
confidence: 99%
“…Recent studies mainly focus on the technical aspects of SC, such as infrastructure optimisation [19], SC facilities [20], or SC solutions like demand and response systems [21]. Other research also tried to include economic considerations of SC [3].…”
Section: Research Demandmentioning
confidence: 99%
“…In this research, polymer electrolyte membranes (PEMEC) electrolysis is applied, which is preferred for seasonal energy storage (as it is applied also by Power-to-Gas Hungary Kft), mainly because of its high flexibility, fit to volatile renewable energy generation, and high technology-readiness level [23]. While hydrogen is going to be used in the next P2G step (methanation), oxygen generation can also be exploited at WWTPs; the efficiency of the aeration system can be increased by injection of oxygen into it [8].…”
Section: Technology Descriptionmentioning
confidence: 99%
“…While the promising role of the P2G technology in the energy sector has been argued comprehensively in recent years (e.g., from the aspect of long-term energy storage [2], system analysis [6] or technological and economic factors [7]), researchers have also started to focus on the role of WWTPs with respect to different aspects of renewable energy transition and power-to-X technologies. Schäfer et al [8] pointed out that WWTPs have notable synergy potential in sector coupling, for example, hydrogen and methane can be produced at WWTPs (with P2G technologies), and the oxygen (as the byproduct of the electrolysis) can be used to enhance purification processes. Gretzschel et al [9] focused on power-to-hydrogen (P2H) technology and the elimination of organic micropollutants at WWTPs, considering the possibility of offering system service, as well: automatic frequency restoration reserve (aFRR), which can provide short-term flexibility for network operators.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the electricity sector driven by renewables, power-to-x technologies can supply the required transformation of energy to the other sectors to substitute fossil-based resources and lead to more stability of the system. A large review of the possible role of WWTPs by means of sector coupling is given in [19]. Practical implementations and their impacts on the processes are depicted, discussed and evaluated.…”
Section: Sector Coupling and Energy Transitionmentioning
confidence: 99%
“…Furthermore, storable methane gas can be produced at WWTPs, which can contribute to an implementation of local heating networks. As explained in detail in [19], an interconnection in many fields of different research sectors is given and it is shown that it is possible and reasonable for WWTPs to contribute with sustainable energy concepts to defossilization. Thus it can be assumed that many WWTPswill be able to support the energy transition with its gas potentials and flexibility options if suitable management concepts are applied (cf.…”
Section: Sector Coupling and Energy Transitionmentioning
confidence: 99%